(untitled) (International Journal of Physiology, 2021)
Introduction: COVID-19 pandemic is spread by droplet infectionwith symptoms of fever, cough, diarrhea,dyspnea, fatigue, myalgia, headache, anosmia and ageusia. Morbidity and mortality is higher among elderly and in patients with comorbidities especially Diabetes Mellitus(DM). Biomarkers of inflammation are potential predictors for prognosis in covid patients. Aim: To analyze the association of NLR in covid 19 patients with symptoms and diabetic status Objective: 1. To studyNLR in covid 19 patients with and without symptoms 2. To study the association of NLR between diabetic and non-diabetic covid 19 patients. 3. To study the association between symptomatology and NLR in diabeticcovid 19 patients. Methodology: 3000 RT-PCR confirmed Covid 19 patients who attended triage op were included afterEthics committee approval.Patients were grouped as patients with and without symptoms and patients with and without DM.The diabetic Covid patients were also analyzed based on the symptoms. Blood samples onreporting were used for analysis of NLR andparameters analyzed using SPSS23.0 version. Result: There is no statistically significant difference in NLR among Covid symptomatic and asymptomatic patients. But NLR is markedly raised in covid symptomatic patients with diabetes mellitus.